A Case Report of Living Donor Liver Transplantation for Fulminant Hepatitis Related to Hepatitis E Virus Infection. (March 2018) - Shimata, Keita; Sugawara, Yasuhiko; Yamamoto, Hidekazu; Okamoto, Hiroaki; Uchida, Koushi; Kawabata, Seiichi; Isono, Kaori; Hayashida, Shintaro; Inomata, Yukihiro
Hepatitis E virus (HEV) infection which may become fulminant, especially in elderly people is more common than previously recognized in develop countries. Here we report successful living-donor liver transplantation (LDLT) in a case of acute liver failure due to HEV. A 63-year-old Japanese man with no previous history of liver disease was admitted for severe acute hepatitis. Detection of anti-HEV immunoglobulin A established a diagnosis of this virus-related liver failure. The patient suffered from hepatic encephalopathy 10 days after symptom onset and underwent LDLT. The patient had an uneventful course. The HEV RNA showed spontaneous negative conversion 10 weeks after LDLT. LDLT led to a successful outcome in a patient with acute liver failure due to HEV infection and regular testing for HEV RNA should be performed until HEV RNA is undetectable.